(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Authentication systems are the protective barrier of any software. The authentication system can be classified as Token based, Biometric based and Knowledge based. This research study is based on knowledge based authentication system. As an initial step the existing knowledge based authentication system has been studied for its highlights, comparative facts, advantages and disadvantages. For acceptance of any secure system the usability aspect is the first step in the authentication process. The various usability evaluation parameters of the existing systems and an approach towards developing a modified usable authentication system have been briefly discussed. Future scope of other dimensions viz. randomness and security and a deep study have been highlighted as the concluding remark of this research work.